Indoors and outdoors: designing mobile experiences for Cité de l’espace - Rennick-Egglestone, Stefan; Roussou, Maria; Brundell, Patrick; Chaffardon, Christophe; Kourtis, Vassilis; Koleva, Boriana; Benford, Steve (NODEM, 2013)
The CHESS project has been working with Cité de l’espace, a space technology centre, to explore the use of tablets and mobile phones to deliver visitor experiences that integrate across multiple experiences. In this paper, we articulate three key challenges present at Cité, describe a prototype experience developed by CHESS, and present a set of observations developed through an evaluation conducted in October 2012.